Lloyd Carpenter Griscom papers - Griscom, Lloyd Carpenter, 1872-1959.
Contains diaries (1901-1921), correspondence (family and general 1900-1951), memoranda (1907-1940), papers concerning an Army War College lecture (1940), biographical materials, newspaper clippings, and broadsides. Mainly related to Griscom's diplomatic career in Iran (1901-1902), Japan (1902-1906), and Italy (1907-1909). Correspondents include Mabel T. Boardman, Arthur Meeker, John J. Pershing, Elihu Root, Francis Lynde Stetson, Wesley W. Stout, and William Howard Taft.
Author, diplomat, lawyer, politician, and soldier.
Keywords: Boardman, Mabel Thorp, -- 1860-1946 -- Correspondence; Meeker, Arthur, -- 1866-1946 -- Correspondence; Pershing, John J. -- 1860-1948 -- Correspondence; Root, Elihu, -- 1845-1937 -- Correspondence; Stetson, Francis Lynde -- Correspondence; Stout, Wesley Winans, -- 1890- -- Correspondence; Taft, William H. -- 1857-1930 -- Correspondence; Army War College (U.S.); Iran -- Foreign relations -- United States; Italy -- Foreign relations -- United States; Japan -- Foreign relations -- United States; United States -- Foreign relations -- Iran; United States -- Foreign relations -- Italy; United States -- Foreign relations -- Japan; Authors; Diplomats; Lawyers; Politicians; Soldiers